PENGARUH KUALITAS, HARGA, DAN DESAIN PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK FORT.ID - Purnomo, Vincent Sebastian (PERFORMA, 2023)
Fashion becomes quite profitable industry due to keep on following trend, not only female fashion that develops rapidly but also male fashion develops, recently a lot of male start paying attention outward appearance. The fashion industry recently gets growth and give quite high contribution towards national income of creative economy gross domestic product (GDP). Fort.id is a company that has been established since February 2018 which runs in fashion field especially in leather craft field by selling products such as clutch and wallet. Sale of Fort.id products get fluctuated so that the researcher needs to know about what things that affect purchase decision of Fort.id products. The purpose of this research is to find out the effect of quality, price, and product design on purchase decision of Fort.id products. This research is quantitative research and the population of this research is Fort.id consumers starting from August 2019 to August 2020. The saturated sample that amounts 35 respondents like stated on customer list in August 2019 to August 2020. The data is processed using multiple regression analysis with SPSS application. The results of this research are quality and product design variables affect positive on purchase decision and price variable does not affect on purchase decision.